Design for automated disassembly: a comparative study of different battery component designs - Hansen, S.; Ohnemüller, G.; Ionescu, Christina; Zorn, Merle; Deeken, Jan-Aut; Rüther, Tom; Mennenga, Mark; Danzer, Michael A.; Flamme, Sabine; Vietor, Thomas; Herrmann, Christoph; Döpper, Frank (International journal of sustainable engineering, 2025)
The feasibility of automated disassembly at a product’s end-of-life stage strongly depends on its design. This relationship is particularly relevant for electric vehicle batteries, for which other design requirements are typically given priority. Consequently, the potential for automated disassembly varies between different battery designs and between the different components. This study investigates the potential for automated disassembly of five EV battery designs currently available on the market. These batteries are subject to disassembly experiments, during which a criteria catalogue is employed to semi-quantitatively compare the individual design characteristics of each individual component. The results of this assessment indicate that the complexity involved in automatically disassembling the components generally increases with the depth of disassembly. Nevertheless, the initial step of the system cover removal appears to be of high importance. It is further identified that the steps involved in the removal of cooling systems, the separation of module housing parts and the cell connector separation are the most critical during disassembly. Based on these findings specific design guidelines are proposed from the best evaluation results of the five disassembly analyses performed.